If it's not what You are looking for type in the equation solver your own equation and let us solve it.
0=3(x-2)(x+4)
We move all terms to the left:
0-(3(x-2)(x+4))=0
We add all the numbers together, and all the variables
-(3(x-2)(x+4))=0
We multiply parentheses ..
-(3(+x^2+4x-2x-8))=0
We calculate terms in parentheses: -(3(+x^2+4x-2x-8)), so:We get rid of parentheses
3(+x^2+4x-2x-8)
We multiply parentheses
3x^2+12x-6x-24
We add all the numbers together, and all the variables
3x^2+6x-24
Back to the equation:
-(3x^2+6x-24)
-3x^2-6x+24=0
a = -3; b = -6; c = +24;
Δ = b2-4ac
Δ = -62-4·(-3)·24
Δ = 324
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{324}=18$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-6)-18}{2*-3}=\frac{-12}{-6} =+2 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-6)+18}{2*-3}=\frac{24}{-6} =-4 $
| 2a+21=75 | | 3x-2=7x-8 | | -5x+44=-31 | | 8z+z=0 | | -12x-45=15 | | 12x-5=5x+2 | | 0.6a-0.4-2.8a=3-8.2 | | 6+1-7x=x-7 | | 5x^2-2x-17=0 | | 6x+10+4x-20+90=180 | | y-2.463=5.987 | | -9=1x+-21 | | (x+1)/2=(3x+7)/5 | | 13=1/6f | | y+5=y+37 | | 9y+5=y+47 | | 1+2xx2x=145 | | 20=11-f-14 | | 5/12b=3/5 | | 8b-22=6b | | -32=63+x | | 5(x-3/5)=-13 | | q+1/7=5/7 | | 3-x+1=6x-1 | | 11n+1=–21 | | 148.5-9.5w=215 | | 3(x-3)+2x=-34 | | 3j^2-16j+16=0 | | 0.8^x=3^x^2 | | 7.614+p=11.305 | | 950-148.5w=215 | | y÷6=42 |